HIV Infection in Iran: An Update on Epidemiology, Testing and Gaps - Seyed Ahmad Seyed Alinaghi; Mohammad Mahdi Roozbahani; Behnam Farhoudi; Seyed Ali Dehghan Manshadi; Shayesteh Jahanfar (Acta Medica Iranica)
The HIV epidemic continues to disproportionately affect young and active individuals in developing and low-income countries, including Iran. Among high-risk populations in Iran, HIV prevalence peaks at 3.5% among people who inject drugs and 2.5% among men who have sex with men. Despite progress in achieving the UNAIDS 95-95-95 targets for HIV diagnosis, treatment, and viral suppression, significant gaps remain in early detection and reaching vulnerable populations, including pre-exposure prophylaxis and targeted outreach to key populations. Education and awareness campaigns are crucial for preventing the spread of HIV, particularly among young people. However, there is a need to improve education and access to information and HIV services for key populations. Expanding HIV testing and counselling services is vital for early diagnosis and treatment. Addressing the issue of late diagnosis, which can negatively impact treatment outcomes and mortality rates, is essential. Integrating HIV services into primary healthcare can improve access and outcomes. A holistic and multi-sectoral approach, encompassing education, prevention, treatment, and care, is necessary to curb the spread of HIV and improve the quality of life for individuals affected by HIV infection in Iran.